(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Maternal health remains a critical global concern, with sustainable development goal 3 aiming to reduce the maternal mortality ratio and ensure universal access to reproductive healthcare by 2030. According to a 2023 report, a woman dies from preventable causes related to pregnancy and childbirth every 2 minutes, and almost 70% of maternal deaths occur in sub-Saharan Africa. The reduction of maternal mortality and promotion of maternal health and well-being are complex tasks. Objective: To understand how a synergistic approach integrating complex interventions’ research, implementation science principles, knowledge translation, and innovative solutions can be leveraged to achieve sustainable improvements in maternal health outcomes in different contexts. Methods: This study employed sequential and iterative critical interpretive synthesis (CIS), integrative literature (ILR) review with multiscale analysis of extant literature on maternal health starting with the landmark Lancet series on “Maternal Survival” 2006 (5 papers); 2016 “Maternal Health” series (6 papers); the 2023 Series – “Maternal health in Perinatal period and Beyond” (4 papers); and health sector strategic plans. Results: Despite knowledge that healthcare is a complex adaptive system (CAS), whereas interventions for maternal health are considered complex interventions, the predominant implementation approaches assume a linear cause-effect approach, leading to the observed stagnation in maternal health. Conclusion: The effectiveness of complex interventions and their success in reaching relevant populations is critically influenced by their implementation in each context. A linear understanding of evidence translation, from ‘bench to bedside’, is naïve. This is because those who deliver, manage, and receive healthcare, negotiate multiple forms and sources of evidence, which complement and compete within a complex system of institutional logics.